Computational thinking in the chemical sciences curriculum - Southam, Daniel; Rohl, Brenda (Creathach Press, 2019)
We aim to support alternative approaches to traditional chemistry curriculum that develop computational thinking skills forecast to be necessary for their future employability. We undertook an exploratory cross-sectional survey of all commencing undergraduate science students at Curtin University to ascertain their self-efficacy beliefs relating to digital and information literacies and used these data to help inform changes to our chemistry curriculum. The findings illustrate that students with higher digital literacy self-efficacy beliefs are more likely to choose a degree that supports these beliefs, and this includes Chemistry and Biochemistry majors at our institution. As a consequence of these observed self-efficacy beliefs, we provide some practical and illustrative examples of how to adapt chemistry curriculum to better harness opportunities for development of computational thinking. Ultimately, we aim to better prepare chemistry graduates by providing multiple opportunities throughout an undergraduate program to support and further develop their computational thinking and digital literacy skills necessary for future employability.